PENGARUH MANAJEMEN WAKTU DAN EFIKASI DIRI PADA HASIL BELAJAR EKONOMI KELAS X SMAN 1 SIDOARJO - Adinda Amelia Putri; Retno Mustika Dewi (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2022)
ABSTRACT This research was carried out because the learning at SMAN 1 Sidoarjo was carried out hybridly during the pandemic. So that is has a shorter allocation of learning time than offline learning. The purpose of this study is to determine the influence of time management and self-efficacy on the learning outcomes of class X economics subjects in SMAN 1 Sidoarjo hybrid learning during the Covid-19 pandemic. Using simple random sampling techniques with a population of 163 students. The study used primary data obtained from questionnaires. The analysis method uses multiple liner regression analysis with the help of the SPPS 24 program. The result of this study partially and simultaneously showed that each of them had a positive and significant influence on time management and self-efficacy on the learning outcomes of class subjects in SMAN 1 Sidoarjo hybrid learning. Keywords: Learning Outcomes, Time Management, Self-Efficacy